Pallidal Deep Brain Stimulation Improves Higher Control of the Oculomotor System in Parkinson's Disease - Antoniades, CA; Rebelo, P; Kennard, C; Aziz, TZ; Green, AL; Fitzgerald, JJ (Society for Neuroscience, 2015)
The frontal cortex and basal ganglia form a set of parallel but mostly segregated circuits called cortico-basal ganglia loops. The oculomotor loop controls eye movements and can direct relatively simple movements, such as reflexive prosaccades, without external help but needs input from "higher" loops for more complex behaviors. The antisaccade task requires the dorsolateral prefrontal cortex, which is part of the prefrontal loop. Information flows from prefrontal to oculomotor circuits in the striatum, and directional errors in this task can be considered a measure of failure of prefrontal control over the oculomotor loop. The antisaccadic error rate (AER) is increased in Parkinson's disease (PD). Deep brain stimulation (DBS) of the subthalamic nucleus (STN) has no effect on the AER, but a previous case suggested that DBS of the globus pallidus interna (GPi) might. Our aim was to compare the effects of STN DBS and GPi DBS on the AER. We tested eye movements in 14 human DBS patients and 10 controls. GPi DBS substantially reduced the AER, restoring lost higher control over oculomotor function. Interloop information flow involves striatal neurons that receive cortical input and project to pallidum. They are normally silent when quiescent, but in PD they fire randomly, creating noise that may account for the degradation in interloop control. The reduced AER with GPi DBS could be explained by retrograde stimulation of striatopallidal axons with consequent activation of inhibitory collaterals and reduction in background striatal firing rates. This study may help explain aspects of PD pathophysiology and the mechanism of action of GPi DBS. Significance statement: Parkinson's disease causes symptoms including stiffness, slowness of movement, and tremor. Electrical stimulation of specific areas deep in the brain can effectively treat these symptoms, but exactly how is not fully understood. Part of the cause of such symptoms may be impairments in the way information flows from one circuit within the brain to another, as a result of overactivity of certain nerve cells. By demonstrating that stimulation of an area called the globus pallidus interna partially reverses deficits in voluntary control of eye movements, this study shows that stimulation can improve information flow between circuits, probably by calming down the overactive cells.